“Mental maps”: Between memorial transcription and symbolic projection - Guelton, Bernard (Frontiers in Psychology, 2023)
The mental map is a notion that lies within the scope of various contexts. The cognitive map, or the concept map – also known as the “heuristic” or “mind” map – are the two distinct contextual meanings covered by the term mental map in the present article. In the mental maps domain, the first major field of study is geography, spatial cognition, and neurophysiology and it aims to understand how the route taken by a subject (or a set of subjects) in space leads to memorization and internal representation(s). In general, the externalization of these representations takes the form of drawings, positioning in a graph, or oral/textual narratives, but it is primarily reflected as a behavior in space that can be recorded as tracking items. A second field of study, one which is geared more towards exploratory and combinatorial uses, is the concept (also heuristic or mind) map which consists in organizing notions, concepts, and information in the form of tree graphs or graphs that can be used to produce diagrams and flowcharts. The aim is projective, for clarification and discovery purposes or for data organization and visualization. To date, very few studies in the literature have examined the similar, overlapping and oppositional features in what is broadly referred to as “representation(s) of space” and “space(s) of representation”. Questions still remain about how to gain a better understanding of the complex notion of the “mental map” and the issues of memorial transcription or “symbolic projection”, as well whether meeting points, and possibly a continuum, can be identified between the two polarities of mental map such as cognitive map and concept map. Through the notion of the cognitive graph, recent advances in the understanding of brain mechanisms have enabled us to holistically address the distinctions between cognitive maps and concept maps as an interconnected and continuous whole.